Effect of Methylene Blue on White Matter Injury after Ischemic Stroke. (2nd February 2021) - Cheng, Quancheng; Chen, Xuhao; Ma, Jiayi; Jiang, Xingyuan; Chen, Jiahui; Zhang, Mengqin; Wu, Yejun; Zhang, Weiguang; Chen, Chunhua
Abstract : Methylene blue, the FDA-grandfathered drug was proved to be neuroprotective in ischemic stroke in rat. However, the mechanism of the protective effect was unknown. In this study, we used different animal models to investigate the effect of MB administration given within and beyond the therapeutic time window on behavioral deficits and infarct volume and related mechanism about the white matter protection. Middle cerebral artery occlusion and reperfusion (MCAO) and photothrombotic middle cerebral artery occlusion (PT-MCAO) models were used. Behavioral deficits and infarct volume were measured by foot fault test, Garcia neurological score, and TTC staining. Black gold staining and western blot were used to evaluate the brain white matter injury. We found that intraperitoneal administration of MB immediately or 24 h after the MCAO or PT-MCAO surgery reduced infarct volume, improved the neurological deficits, and reduced the white matter injury via myelin basic protein (BMP) protection. These findings suggested that MB relieved the white matter injury besides neuronal protection and has potential therapeutic effects on ischemic stroke.